Preparation method of wave-absorbing metamaterial structure resistant to high-energy laser irradiation

By surface treatment of quartz fibers and inorganic fillers, combined with electrochemical corrosion, laser etching and hot pressing forming processes, an absorbing metamaterial structure that is resistant to high-energy laser radiation is prepared, solving the problem of existing materials in high-energy laser radiation The problem of easy damage has achieved better radiation resistance and wave absorption performance.

CN119458950APending Publication Date: 2025-02-18NO 33 RES INST OF CHINA ELECTRONICS TECHNOOGY GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411654587.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing wave absorbing metamaterial structure is prone to combust, damage and damage under high-energy laser radiation, limiting the survivability of drones and other equipment.

Method used

The quartz fiber and inorganic filler are surface treated with silane coupling agent and mixed with silicone resin. The periodic structural unit layer is prepared by electrochemical corrosion or laser etching, and the absorption with high energy-resistant laser radiation is prepared by combining the hot pressing process. Wave metamaterial structure.

Benefits of technology

While maintaining the original physical and mechanical properties, the material's high-energy laser radiation resistance is significantly improved, and the width of the absorbing frequency band and the overall mechanical strength are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic metamaterials, in particular to a preparation method of a wave-absorbing metamaterial structure resistant to high-energy laser irradiation. Pretreating the inorganic filler and the quartz fiber cloth; etching the resistive film to obtain periodic structure unit layers B1 and B2; s4, mixing a resin matrix with a curing agent to obtain a mixture C; immersing the pretreated inorganic filler into the mixture C to obtain three mixtures D1, D2 and D3 with different proportions; immersing the pretreated quartz fiber cloth into the mixture D1, the mixture D2 and the mixture D3 to obtain quartz fiber cloth prepregs E1, E2 and E3; coating a release agent in the mold, laying a resistive film with polyimide as a base material from bottom to top, and compacting E1, B1, E2, B2 and E3 for mold closing; heating and pressurizing the hot press to keep curing; and then curing to obtain the high-energy laser irradiation resistant wave-absorbing metamaterial structure. Cooperative regulation and control of laser high reflection, high temperature resistance, high heat insulation / ablation resistance properties and wave absorbing performance are achieved, and mechanical properties are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic metamaterials, and more specifically, to a method for preparing a wave-absorbing metamaterial structure resistant to high-energy laser irradiation. Background Art

[0002] At present, based on the requirements of lightweight and broadband wave-absorbing design, wave-absorbing metamaterial structure has become one of the main key composite materials for the load-bearing / sub-load-bearing structural parts of the fuselage, wings and other equipment of drones. It has the advantages of strong multifunctional integrated designability, good wave-absorbing performance, high mechanical strength, low density, and good adaptability to extreme environments.

[0003] Generally speaking, ordinary absorbing metamaterial structures with resin-based reinforced composite materials as the dielectric layer are very prone to burning, damage and destruction under high-energy laser irradiation. Their extensive use in the load-bearing / secondary load-bearing structures of equipment such as the fuselage and wings of drones has greatly limited the survivability of drones and other equipment under high-energy laser irradiation.

[0004] As the power density of high-energy laser irradiation continues to increase, the widespread harm it brings to equipment such as drones is becoming increasingly serious. Conventional absorbing metamaterial structures with resin-based composite materials as the dielectric layer can hardly reflect and absorb high-energy lasers. Experiments have shown that even at tens of W / cm 2 It will also burn through instantly under laser irradiation and has no protection at all.

[0005] In recent years, in order to improve the high-energy laser irradiation resistance of absorbing metamaterial structures, researchers have mostly adopted methods such as coating the surface of absorbing metamaterial structures with metal reflective layers or coating the surface with high-energy laser protective coatings. The strong reflection characteristics of the metal reflective layer coated on the surface greatly reduce the broadband and efficient absorption of electromagnetic waves by the absorbing metamaterial structure; the high-energy laser protective coating coated on the surface, although it does not strongly reflect electromagnetic waves, significantly affects the interface characteristics of the absorbing metamaterial structure, resulting in a mismatch in the interface impedance characteristics of the absorbing metamaterial structure, which also affects the broadband and efficient absorption of electromagnetic waves by the absorbing metamaterial structure.

[0006] In order to achieve compatible design of high-energy laser resistance, broadband absorption and mechanical strength in the prior art, researchers often use methods such as plating a metal reflective layer on the surface of the absorbing metamaterial structure or coating the surface with a high-energy laser protective coating. Although plating a metal high-reflective layer on the surface of the absorbing metamaterial structure can significantly improve the ability to withstand high-energy laser irradiation, the underlying absorbing metamaterial structure cannot play the role of broadband absorption, resulting in the overall electromagnetic signal characteristics of the equipment being prominent, which is easily detected by radar reconnaissance, restricting the survivability of equipment such as drones. Although the negative impact of coating the surface of the absorbing metamaterial structure with a high-energy laser protective coating on the impedance mismatch of the underlying absorbing metamaterial structure is not as great as plating the metal high-reflective layer, there are still problems such as easy delamination and shedding of the coating and obvious overall weight gain / thickness. Summary of the invention

[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one aspect of the present invention aims to provide a method for preparing a high-energy laser irradiation-resistant absorbing metamaterial structure. The specific steps of the preparation method are as follows: S1. dilute the silane coupling agent with ethanol, soak the inorganic filler in it, and dry it after soaking; S2. dilute the silane coupling agent with ethanol, soak the quartz fiber cloth in it, and dry it after soaking to obtain quartz fiber cloth A; S3. According to the design requirements of the absorbing metamaterial structure, the resistive film having a polyimide substrate is etched by an electrochemical etching process or a laser etching process to obtain periodic structural unit layers B1 and B2; S4. The resin matrix and the curing agent are mixed to obtain a mixture C; S5. The inorganic filler obtained by the treatment in S1 is immersed in the prefabricated mixture C in S4, and the resin matrix and the inorganic filler are mixed in 3 different proportions to obtain a mixture D1, D2, and D3; S6. Immerse the quartz fiber cloth A obtained in S2 into the mixture D1, D2, and D3 prepared in S5, and dry to obtain quartz fiber cloth prepregs E1, E2, and E3; S7. According to the requirements of the design of the wave-absorbing metamaterial structure, a release agent is applied to the mold, and a resistor film with a polyimide substrate, a quartz fiber cloth prepreg E1 prepared by S6, a periodic structure unit layer B1 prepared by S3, a quartz fiber cloth prepreg E2 prepared by S6, a periodic structure unit layer B2 prepared by S3, and a quartz fiber cloth prepreg E3 prepared by S6 are laid in this order from bottom to top, and the mold is compacted and closed; with the mass fraction of resin being 100 parts, the mass fraction of quartz fiber in the quartz fiber prepreg is controlled to be 30-40 parts, the mass fraction of inorganic filler is 30-40 parts, and the mass fraction of curing agent is 0.5-2.0 parts, and from bottom to top, the mass fraction of the woven fabric of each layer of quartz fiber cloth gradually decreases; the mass fraction of the wave-absorbing functional filler in the mixture D: manganese zinc ferrite, strontium barium ferrite gradually decreases; the mass fraction of the high-energy laser irradiation resistant functional filler: silicon carbide whiskers, aluminum oxide, and silicon dioxide gradually increases; S8. Place the mold on the hot press and pressurize to maintain solidification; S9. After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0008] Optimized, the silane coupling agent in S1 is any one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560) and γ-methacryloxypropyltrimethoxysilane (KH570); the inorganic filler is a high-energy laser irradiation resistant filler and an electromagnetic functional filler; the high-energy laser irradiation resistant filler is specifically any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the electromagnetic functional filler is specifically any one or more of manganese zinc ferrite and strontium barium ferrite; the mass ratio of silane coupling agent to ethanol is 3 to 5:100, the immersion time is 0.5 to 2 hours, the immersion temperature is room temperature, and the drying temperature is 50°C to 60°C.

[0009] Optimized, the mass ratio of silane coupling agent to ethanol in S2 is 3-5:100, the soaking time is 0.5-2h, the soaking temperature is room temperature, and the drying temperature is 50°C-60°C; the surface density of the quartz fiber cloth is 100g / m 2 , 120g / m 2 , 150g / m 2 , 200g / m 2 or 250g / m 2 .

[0010] Optimally, the material of the resistor film for preparing the periodic structure unit layer in S3 is copper, silver, gold, aluminum or other metal materials, indium tin oxide, zinc oxide or other conductive oxides, conductive silver paste, conductive ink, conductive carbon film, or any one or more thereof; the conductivity range is 1×10-9 ~1×10 -5 S / m, thickness range is 50nm~100μm.

[0011] Optimized, the unit structure form in the periodic structure unit layer in S3 is any one or more of a cross, snowflake, Jerusalem, I-shaped, I-shaped, H-shaped, circular, and their derivative, complementary or iterative structures.

[0012] Optimally, the mass ratio of the resin matrix to the curing agent in S4 is 100:0.5-2.0; the resin matrix is ​​any one or more of silicone resin, phenolic resin, and epoxy resin; the curing agent is any one or more of vinyltrimethoxysilane, benzenesulfonic acid, and benzoyl peroxide.

[0013] Optimized, the three different ratios in S5 are in a mass ratio of the resin matrix to the inorganic filler of 100:30-50; the inorganic filler in S5 is a high-energy laser radiation resistant filler and an electromagnetic functional filler; the high-energy laser radiation resistant filler is specifically any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the electromagnetic functional filler is specifically any one or more of manganese zinc ferrite and strontium barium ferrite.

[0014] Optimally, the mass ratio of the resin matrix to the quartz fiber cloth in S6 is 100:30-40, and the drying temperature is 50°C-60°C.

[0015] Optimized, in S8, the hot press is heated to 120° C. to 125° C., pressurized to 20 MPa to 25 MPa, and the curing time is 1.5 h to 2 h.

[0016] Optimally, the post-curing temperature in S9 is 120° C. to 150° C., and the post-curing time is 24 h to 48 h.

[0017] The beneficial effects of the present invention are as follows: Compared with the traditional quartz fiber reinforced wave-absorbing composite material, the present invention uses inorganic fillers such as silicon carbide whiskers, zirconium oxide, aluminum oxide, silicon dioxide, manganese zinc ferrite, strontium barium ferrite, etc. as the main high-energy laser irradiation-resistant and broadband wave-absorbing fillers, which can maintain the original physical and mechanical properties while having the advantages of low density, easy molding, strong high-energy laser irradiation resistance, wide wave-absorbing frequency band, etc.; in the preparation method, firstly, the quartz fiber and the inorganic fillers such as silicon carbide whiskers, zirconium oxide, aluminum oxide, silicon dioxide, manganese zinc ferrite, strontium barium ferrite, etc. are surface treated with an ethanol solution of a silane coupling agent, Then mixed with silicone resin, phenolic resin or epoxy resin, so that various functional fillers are dispersed more evenly and stably in the resin matrix, and the interface bonding force is stronger, which is conducive to improving the mechanical strength of the composite material; taking into full consideration the thermal ablation and thermal decomposition process of the material under high-energy laser irradiation, based on the design principle of absorbing metamaterial structure, the type, chemical formula and compound ratio range of high-energy laser irradiation resistant fillers and broadband absorbing fillers of the dielectric layer in the absorbing metamaterial structure are proposed and optimized in a gradient manner, and then the gradient of the electromagnetic parameters of the dielectric layer is realized according to the design requirements of the absorbing metamaterial structure. The optimized absorbing metamaterial structure can meet the different functional / performance design requirements of the load-bearing / sub-load-bearing structural parts of the fuselage, wings and other equipment of drones, and realize the integrated design and precision molding of high-energy laser resistance, broadband absorption and mechanical strength. In the specific implementation process, the electrochemical corrosion process or laser etching process is used to make the unit interface in the periodic structure unit layer clear and flat, and the surface resistance distribution is stable. The surface treatment with coupling agent makes the dispersion of various functional fillers in the resin matrix more uniform and stable, and the interface bonding force is stronger; the hot pressing molding process is used for one-time molding, which simplifies the preparation process and is conducive to improving the mechanical strength of the composite material. Compared with the conventional technical route of optimizing the chemical formula to improve the high-energy laser radiation resistance in the prior art, the wave-absorbing metamaterial structure proposed in the patent of this invention, although the surface is also partially damaged by high-energy laser radiation, has little effect on the overall wave-absorbing effect, showing good resistance to high-energy laser radiation.

[0018] Additional aspects and advantages of the invention will become apparent from the following description, or may be learned by practice of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 It is a structural diagram of a hexagonal high-energy laser irradiation-resistant absorbing metamaterial structure prepared by the present invention; Figure 2 It is a structural diagram of a circular high-energy laser irradiation-resistant wave-absorbing metamaterial structure prepared by the present invention; Figure 3It is a structural diagram of the cross-shaped high-energy laser irradiation-resistant wave-absorbing metamaterial structure prepared by the present invention; Figure 4 This is a reflectivity test curve diagram before and after irradiation of the second embodiment of the present invention; Figure 5 This is a reflectivity test curve diagram of Example 7 of the present invention before and after irradiation. DETAILED DESCRIPTION

[0020] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from the description. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0022] The structure of the wave-absorbing metamaterial that can withstand high-energy laser irradiation is shown in the figure. Figure 1-3 shown.

[0023] Embodiment 1 S1: dilute the silane coupling agent KH550 and ethanol in a mass ratio of 3:100, and soak the high-energy laser irradiation resistant filler silicon carbide whisker, zirconium oxide, aluminum oxide and electromagnetic functional filler manganese zinc ferrite in the above solution in a mass ratio of 1:1:1:3 for 0.5 h at room temperature, and dry at 50°C after treatment; S2 dilutes the silane coupling agent KH550 and ethanol in a mass ratio of 3:100, and 2 The quartz fiber cloth is immersed in the above solution for 0.5 h at room temperature, and dried at 50°C to obtain quartz fiber cloth A. S3 uses an electrochemical etching process to etch the copper film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0024] S4: a mixture C obtained by mixing silicone resin and vinyl trimethylsiloxane in a mass ratio of 100:0.5; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4, and mixing the silicone resin and the inorganic filler in a mass ratio of 100:50, 100:40, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of the silicone resin matrix to the quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, in this order, a copper film with a polyimide substrate, quartz fiber cloth prepreg E1 prepared by S6, a periodic structure unit layer B1 prepared by S3, quartz fiber cloth prepreg E2 prepared by S6, a periodic structure unit layer B2 prepared by S3, and quartz fiber cloth prepreg E3 prepared by S6 are laid, and the mold is compacted and closed; S8: Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 120° C. for 48 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0025] Embodiment 2 S1: dilute the silane coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak the high-energy laser irradiation resistant filler silicon carbide whisker, zirconium oxide, aluminum oxide and electromagnetic functional filler strontium barium ferrite in the above solution in a mass ratio of 1:1:2:2 for 1 hour at room temperature, and dry at 50°C after treatment; S2 dilutes the silane coupling agent KH560 and ethanol in a mass ratio of 4:100, and 2 The quartz fiber cloth is immersed in the above solution for 1 hour at room temperature, and dried at 50°C to obtain quartz fiber cloth A. S3 uses an electrochemical etching process to etch the aluminum film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0026] S4: mixing phenolic resin and benzenesulfonic acid in a mass ratio of 100:0.5 to obtain a mixture C; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4; the phenolic resin and the inorganic filler are mixed in a mass ratio of 100:50, 100:40, and 100:40 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of phenolic resin to quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, lay the aluminum film with a polyimide substrate, the quartz fiber cloth prepreg E1 prepared by S6, the periodic structure unit layer B1 prepared by S3, the quartz fiber cloth prepreg E2 prepared by S6, the periodic structure unit layer B2 prepared by S3, and the quartz fiber cloth prepreg E3 prepared by S6, and compact and close the mold; S8: Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150° C. for 24 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0027] Embodiment 3 S1: dilute silane coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak high-energy laser irradiation resistant filler silicon carbide whisker, aluminum oxide and electromagnetic functional filler manganese zinc ferrite and strontium barium ferrite in the above solution in a mass ratio of 1:1:0.25:0.25 for 1.5 hours at room temperature, and dry at 50°C after treatment; S2 dilutes the silane coupling agent KH570 and ethanol in a mass ratio of 5:100, and mixes the surface density of 150g / cm 2 The quartz fiber cloth is immersed in the above solution for 1.5 hours at room temperature, and dried at 60°C to obtain quartz fiber cloth A. S3 uses a laser etching process to etch the conductive carbon film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0028] S4: mixing the epoxy resin matrix and benzoyl peroxide in a mass ratio of 100:1 to obtain a mixture C; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4, and mixing the epoxy resin and the inorganic filler in a mass ratio of 100:45, 100:40, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of epoxy resin matrix to quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, lay the conductive carbon film with a polyimide substrate, the quartz fiber cloth prepreg E1 prepared by S6, the periodic structure unit layer B1 prepared by S3, the quartz fiber cloth prepreg E2 prepared by S6, the periodic structure unit layer B2 prepared by S3, and the quartz fiber cloth prepreg E3 prepared by S6, and compact and close the mold; S8: Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 125° C. for 48 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0029] Embodiment 4 S1: dilute the silane coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak the high-energy laser irradiation resistant fillers silicon carbide whiskers, zirconium oxide, silicon dioxide and electromagnetic functional fillers manganese zinc ferrite and strontium barium ferrite in the above solution in a mass ratio of 1:0.5:0.5:0.2:0.1 for 2 hours at room temperature, and dry at 60°C after treatment; S2 dilutes the silane coupling agent KH560 and ethanol in a mass ratio of 4:100, and 2 The quartz fiber cloth is immersed in the above solution for 2 hours at room temperature, and dried at 60°C to obtain quartz fiber cloth A. S3 uses an electrochemical etching process to etch the copper film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0030] S4: a mixture C obtained by mixing phenolic resin and benzenesulfonic acid in a mass ratio of 100:1.5; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4; the phenolic resin and the inorganic filler are mixed in a mass ratio of 100:45, 100:40, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of the phenolic resin matrix to the quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, in this order, a copper film with a polyimide substrate, quartz fiber cloth prepreg E1 prepared by S6, a periodic structure unit layer B1 prepared by S3, quartz fiber cloth prepreg E2 prepared by S6, a periodic structure unit layer B2 prepared by S3, and quartz fiber cloth prepreg E3 prepared by S6 are laid, and the mold is compacted and closed; S8: Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150° C. for 24 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0031] Embodiment 5 S1: dilute the silane coupling agent KH570 and ethanol in a mass ratio of 5:100, and immerse the high-energy laser irradiation resistant filler silicon carbide whisker, silicon dioxide and electromagnetic functional filler manganese zinc ferrite and strontium barium ferrite in the above solution in a ratio of 1:1:1:1 for 2 hours at room temperature, and dry at 60°C after treatment; S2 dilutes the silane coupling agent KH570 and ethanol in a mass ratio of 5:100, and mixes the surface density of 250g / cm 2 The quartz fiber cloth is immersed in the above solution for 2 hours at room temperature, and dried at 60°C to obtain quartz fiber cloth A. S3 uses an electrochemical etching process to etch the aluminum film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0032] S4: a mixture C obtained by mixing silicone resin and vinyl trimethylsiloxane in a mass ratio of 100:2; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4, and mixing the silicone resin and the inorganic filler in a mass ratio of 100:40, 100:30, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of silicone resin to quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, lay the aluminum film with a polyimide substrate, the quartz fiber cloth prepreg E1 prepared by S6, the periodic structure unit layer B1 prepared by S3, the quartz fiber cloth prepreg E2 prepared by S6, the periodic structure unit layer B2 prepared by S3, and the quartz fiber cloth prepreg E3 prepared by S6, and compact and close the mold; S8: Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 120° C. for 48 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0033] Embodiment 6 S1: dilute the silane coupling agent KH550 and ethanol in a mass ratio of 4:100, and soak the high-energy laser irradiation resistant fillers silicon carbide whiskers, zirconium oxide, silicon dioxide and electromagnetic functional fillers manganese zinc ferrite and strontium barium ferrite in the above solution in a mass ratio of 1:1:1:10:10 for 1.5 hours at room temperature, and dry at 60°C after treatment; S2 dilutes the silane coupling agent KH550 and ethanol in a mass ratio of 4:100, and the surface density is 150g / cm 2 , 200g / cm 2 , 250g / cm 2 The quartz fiber cloths were immersed in the above solution for 0.5 h at room temperature and dried at 50°C to obtain quartz fiber cloths A1, A2 and A3; S3 uses a laser etching process to etch the conductive carbon film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0034] S4: epoxy resin and vinyl trimethylsiloxane are mixed in a mass ratio of 100:0.5 to obtain a mixture C; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4, and mixing the epoxy resin and the inorganic filler in a mass ratio of 100:50, 100:40, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloths AA1, A2, and A3 processed in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of epoxy resin to quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, lay the conductive carbon film with a polyimide substrate, the quartz fiber cloth prepreg E1 prepared by S6, the periodic structure unit layer B1 prepared by S3, the quartz fiber cloth prepreg E2 prepared by S6, the periodic structure unit layer B2 prepared by S3, and the quartz fiber cloth prepreg E3 prepared by S6, and compact and close the mold; S8: Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 125° C. for 48 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0035] Embodiment 7 S1: dilute silane coupling agent KH550 and ethanol in a mass ratio of 5:100, and soak high-energy laser irradiation resistant filler silicon carbide whisker, aluminum oxide and electromagnetic functional filler manganese zinc ferrite and strontium barium ferrite in the above solution in a mass ratio of 1:1.5:5:5 for 2 hours at room temperature, and dry at 60°C after treatment; S2 dilutes the silane coupling agent KH550 and ethanol in a mass ratio of 5:100, and sets the surface density to 100 g / cm 2 , 120g / cm 2 , 150g / cm 2 The quartz fiber cloths were immersed in the above solution for 2 hours at room temperature, and dried at 60°C to obtain quartz fiber cloths A1, A2, and A3; S3 uses an electrochemical etching process to etch the copper film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2; S4: a mixture C obtained by mixing silicone resin and vinyl trimethylsiloxane in a mass ratio of 100:2; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4, and mixing the silicone resin and the inorganic filler in a mass ratio of 100:45, 100:40, and 100:35 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloths AA1, A2, A3 processed in S2 into the mixtures D1, D2, D3 prepared in S5, respectively, with the mass ratio of silicone resin to quartz fiber cloth being 100:30, 100:35, 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, in this order, a copper film with a polyimide substrate, quartz fiber cloth prepreg E1 prepared by S6, a periodic structure unit layer B1 prepared by S3, quartz fiber cloth prepreg E2 prepared by S6, a periodic structure unit layer B2 prepared by S3, and quartz fiber cloth prepreg E3 prepared by S6 are laid, and the mold is compacted and closed; S8: Heat the hot press to 150°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 120° C. for 48 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0036] Embodiment 8 S1: dilute the silane coupling agent KH570 and ethanol in a mass ratio of 3.5:100, and soak the high-energy laser irradiation resistant fillers silicon carbide and alumina and the electromagnetic functional fillers manganese zinc ferrite and strontium barium ferrite in the above solution in a mass ratio of 1:1:2:2 for 0.5 h at room temperature, and dry at 50°C after treatment; S2 dilutes the silane coupling agent KH570 and ethanol in a mass ratio of 3.5:100, and the surface density is 120g / cm 2 , 150g / cm 2 , 200g / cm 2 The quartz fiber cloths were immersed in the above solution for 0.5 h at room temperature and dried at 50°C to obtain quartz fiber cloths A1, A2 and A3; S3 uses a laser etching process to etch the conductive carbon film whose substrate is polyimide to obtain periodic structural unit layers B1 and B2.

[0037] S4: a mixture C obtained by mixing phenolic resin and benzenesulfonic acid in a mass ratio of 100:2; S5: immersing the inorganic filler treated in S1 into the mixture C prepared in S4; the phenolic resin and the inorganic filler are mixed in a mass ratio of 100:45, 100:40, and 100:30 to obtain mixtures D1, D2, and D3; S6: immersing the quartz fiber cloth A obtained in S2 into the mixtures D1, D2, and D3 prepared in S5, respectively, with the mass ratio of phenolic resin to quartz fiber cloth being 100:30, 100:35, and 100:40, and drying at 50-60° C. to obtain quartz fiber cloth prepregs E1, E2, and E3; S7, according to the structural design requirements of the absorbing metamaterial, in the mold coated with a release agent, from bottom to top, lay the conductive carbon film with a polyimide substrate, the quartz fiber cloth prepreg E1 prepared by S6, the periodic structure unit layer B1 prepared by S3, the quartz fiber cloth prepreg E2 prepared by S6, the periodic structure unit layer B2 prepared by S3, and the quartz fiber cloth prepreg E3 prepared by S6, and compact and close the mold; S8: Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After S9 curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150° C. for 24 hours to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

[0038] The materials prepared in Example 2 and Example 7 were selected for irradiation, and the reflectivity test curves before and after the irradiation were as follows: Figure 4 and Figure 5 shown.

[0039] Depend on Figure 4 It can be seen that after 500W / cm 2 After 5s of high-energy laser irradiation, the absorption performance of the high-energy laser irradiation absorbing metamaterial structure at 10GHz showed a downward trend, from -22.77dB to -20dB, and the absorption peak-to-peak value shifted to high frequency, from 10GHz (-22.77dB) to 10.7GHz (-22.26dB). The reason is that after high-energy laser irradiation, the phenolic resin undergoes different degrees of "carbonization", which causes the surface impedance matching characteristics to mismatch and the dielectric properties of the material to change, resulting in the absorption peak-to-peak value shifting to high frequency.

[0040] Depend on Figure 5 It can be seen that after 500W / cm 2 After 5s of high-energy laser irradiation, the absorption peak value of the high-energy laser irradiation absorbing metamaterial structure at 11.49GHz decreased from -15.97dB to -14.78dB, and the absorption peak value shifted to low frequency from 11.49GHz (-15.97dB) to 11.26GHz (-16.95dB). The reason is that after high-energy laser irradiation, the silicone resin undergoes a certain degree of "porcelainization", which causes the surface impedance matching characteristics to mismatch and the dielectric properties of the material to change, resulting in the absorption peak value shifting to low frequency.

[0041] Therefore, although the surface of the high-energy laser irradiation-resistant absorbing metamaterial structure prepared by the present invention is partially damaged by high-energy laser irradiation, the impact on the overall absorbing effect is relatively small, showing good high-energy laser irradiation resistance.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may also have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure, characterized in that: The specific steps of the preparation method are as follows: S1. dilute the silane coupling agent with ethanol, soak the inorganic filler in it, and dry it after soaking; S2. dilute the silane coupling agent with ethanol, soak the quartz fiber cloth in it, and dry it after soaking to obtain quartz fiber cloth A; S3. The resistive film having a polyimide substrate is etched by an electrochemical etching process or a laser etching process to obtain periodic structural unit layers B1 and B2; S4. The resin matrix and the curing agent are mixed to obtain a mixture C; S5. The inorganic filler obtained by the treatment in S1 is immersed in the prefabricated mixture C in S4, and the resin matrix and the inorganic filler are mixed in 3 different proportions to obtain a mixture D1, D2, and D3; S6. Immerse the quartz fiber cloth A obtained in S2 into the mixture D1, D2, and D3 prepared in S5, and dry to obtain quartz fiber cloth prepregs E1, E2, and E3; S7. Apply a release agent to the mold, and lay the polyimide substrate resistor film, the quartz fiber cloth prepreg E1 prepared in S6, the periodic structure unit layer B1 prepared in S3, the quartz fiber cloth prepreg E2 prepared in S6, the periodic structure unit layer B2 prepared in S3, and the quartz fiber cloth prepreg E3 prepared in S6 from bottom to top, and compact and close the mold; S8. Place the mold on the hot press and pressurize to maintain solidification; S9. After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser irradiation-resistant absorbing metamaterial structure is taken out of the mold and placed in an oven for post-curing to obtain a high-energy laser irradiation-resistant absorbing metamaterial structure.

2. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The silane coupling agent in S1 is any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane; the inorganic filler is a high-energy laser irradiation resistant filler and an electromagnetic functional filler; the high-energy laser irradiation resistant filler is specifically any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the electromagnetic functional filler is specifically any one or more of manganese zinc ferrite and strontium barium ferrite; the mass ratio of silane coupling agent to ethanol is 3 to 5:100, the immersion time is 0.5 to 2 hours, the immersion temperature is room temperature, and the drying temperature is 50°C to 60°C.

3. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The mass ratio of silane coupling agent to ethanol in S2 is 3-5:100, the soaking time is 0.5-2h, the soaking temperature is room temperature, and the drying temperature is 50°C-60°C; the surface density of the quartz fiber cloth is 100g / m 2 , 120g / m 2 , 150g / m 2 , 200g / m 2 or 250g / m 2 .

4. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The material of the resistor film for preparing the periodic structure unit layer in S3 is any one or more of copper, silver, gold, aluminum or other metal materials, indium tin oxide, zinc oxide or other conductive oxides, conductive silver paste, conductive ink, and conductive carbon film; the conductivity range is 1×10 -9 ~1×10 -5 S / m, thickness range is 50nm~100μm.

5. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The unit structure in the periodic structure unit layer in S3 is in the form of a cross, a snowflake, a Jerusalem shape, an I shape, an I shape, an H shape, a circle, and any one or more of their derivative, complementary or iterative structures.

6. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The mass ratio of the resin matrix to the curing agent in S4 is 100:0.5-2.0; the resin matrix is ​​any one or more of silicone resin, phenolic resin, and epoxy resin; the curing agent is any one or more of vinyltrimethoxysilane, benzenesulfonic acid, and benzoyl peroxide.

7. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The three different proportions in S5 are in a mass ratio of the resin matrix to the inorganic filler of 100:30 to 50; the inorganic filler in S5 is a high-energy laser radiation resistant filler and an electromagnetic functional filler; the high-energy laser radiation resistant filler is specifically any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the electromagnetic functional filler is specifically any one or more of manganese zinc ferrite and strontium barium ferrite.

8. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The mass ratio of the resin matrix to the quartz fiber cloth in S6 is 100:30-40, and the drying temperature is 50°C-60°C.

9. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: In S8, the hot press is heated to 120° C. to 125° C., pressurized to 20 MPa to 25 MPa, and the curing time is 1.5 h to 2 h.

10. The method for preparing a high-energy laser irradiation-resistant wave-absorbing metamaterial structure according to claim 1, characterized in that: The post-curing temperature in S9 is 120° C. to 150° C., and the post-curing time is 24 h to 48 h.